2017
DOI: 10.1186/s13104-017-2909-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of tuberculin skin test for assessment of immune recovery among previously malnourished children in Ethiopia

Abstract: ObjectiveTo compare levels of immunity in children recovering from severe acute malnutrition (cases) against those of community controls (controls).ResultsAt baseline children recovering from severe acute malnutrition had lower, mid upper arm circumference (122 mm for cases and 135 mm for controls; p < 0.001), weight-for-height Z-score (− 1.0 for cases and − 0.5 for controls; p < 0.001), weight-for-age Z-score (− 2.8 for cases and − 1.1 for controls; p < 0.001) and height/length-for-age Z-score (− 3.6 for case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…This study also provided evidence that current anthropometric discharge criteria are not a good proxy for attainment of homeostasis for iron, with anthropometric discharge criteria being met before a significant proportion of children attains replenished BIS, especially those who were depleted at the start of treatment. Similar issues have been shown in a recent study on immunity in children recovering from SAM [92], and taken together indicate the need for further research to determine the optimum criteria of discharging children that takes into account the fact that RUTF intake should not be prolonged unnecessarily given its high content of fat and other nutrients, and the need to minimize risk of relapse due to excessive morbidity. In parallel to the determination of new discharge criteria, there is a need to accelerate research aiming at determining which follow up intervention may ensure post-discharge recovery of iron homeostasis.…”
Section: Discussionsupporting
confidence: 59%
“…This study also provided evidence that current anthropometric discharge criteria are not a good proxy for attainment of homeostasis for iron, with anthropometric discharge criteria being met before a significant proportion of children attains replenished BIS, especially those who were depleted at the start of treatment. Similar issues have been shown in a recent study on immunity in children recovering from SAM [92], and taken together indicate the need for further research to determine the optimum criteria of discharging children that takes into account the fact that RUTF intake should not be prolonged unnecessarily given its high content of fat and other nutrients, and the need to minimize risk of relapse due to excessive morbidity. In parallel to the determination of new discharge criteria, there is a need to accelerate research aiming at determining which follow up intervention may ensure post-discharge recovery of iron homeostasis.…”
Section: Discussionsupporting
confidence: 59%
“…They concluded that the incidence of anergy increased with the duration of dialysis. Delayed cutaneous hypersensitivity to microbial or protein antigens is commonly depressed in uremic patients (50-60%) compared to healthy controls [1,[3][4][5]10]. In our study, we found that the prevalence of PPD positivity in chronic HD and PD patients was %46.6 and %53.3, respectively.…”
Section: Discussionmentioning
confidence: 44%
“…However, the major defect is generally detected in the cellular immune system in which T-lymphocytes have an important role [2]. Defective cell-mediated immunity, as reflected by anergy to multiple skin test antigens, is well documented in patients with protein-calorie malnutrition [3]. Skin test anergy is also common in patients with uremia and during maintenance hemodialysis treatment [4].…”
Section: Introductionmentioning
confidence: 99%
“…High levels of morbidity, in particular diarrhoeal and respiratory illnesses, were reported in all three studies that measured morbidity [ 28 , 31 , 33 ]. A study in Ethiopia that followed-up children six months post-discharge found that there was approximately a 1.7 times higher incidence of fever, diarrhoea and cough in children discharged as cured compared to controls [ 39 ]. The synergistic effect of malnutrition and infection on risk of mortality is well-documented, and this review furthermore highlights the potential need for additional care for recovered malnourished children in order to prevent infection, as vulnerability to infection is still present despite recovery in WHZ [ 40 ].…”
Section: Discussionmentioning
confidence: 99%